2017
DOI: 10.5935/0101-2800.20170076
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with hospital mortality in renal transplant patients admitted to the intensive care unit with acute respiratory failure

Abstract: Keywords: intensive care units; kidney transplantation; respiratory insufficiency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…The present study showed that the chance of an individual with heart failure dying or going to the ICU is 18.3 times greater than that of an individual without heart failure (Table 4). Although, several studies have compared the clinical outcomes of patients who underwent kidney transplantation [9][10][11][12][13]. No evidence addresses the impact of heart failure on the death and ICU stay in pulmonary infection post-transplant.…”
Section: Discussionmentioning
confidence: 99%
“…The present study showed that the chance of an individual with heart failure dying or going to the ICU is 18.3 times greater than that of an individual without heart failure (Table 4). Although, several studies have compared the clinical outcomes of patients who underwent kidney transplantation [9][10][11][12][13]. No evidence addresses the impact of heart failure on the death and ICU stay in pulmonary infection post-transplant.…”
Section: Discussionmentioning
confidence: 99%
“…As per our study, various studies have shown that advanced graft dysfunction is significantly associated with mortality in RTR. [ 27 28 ]…”
Section: Discussionmentioning
confidence: 99%
“…Both in-hospital and 90-day mortality rates were 22.5% [23]. A more recent retrospective study of 183 KTRs admitted to the ICU for acute respiratory failure found the need for vasopressor drugs [odds ratio (OR) 8.13, P < 0.001], mechanical ventilation (OR 3.87, P ¼ 0.016) and a Simplified Acute Physiology Score (SAPS) 3 (OR 1.04, P ¼ 0.045) were associated with mortality in the multivariate analysis [24].…”
Section: Pneumoniasmentioning
confidence: 99%